APPLICATION OF DIGITAL IMAGE PROCESSING METHODS FOR OBTAINING CONTOURS OF OBJECTS ON ULTRASOUND IMAGES OF THE HIP JOINT - Ratushnyi, Pavlo; Bilynskyi, Yosyp; Zhyvotivskyi, Stepan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
In this work, the problems of research of ultrasonic images of joints are formulated. It is that for early diagnosis of developmental disorders of the hip joints needs to take frequent pictures, and the least harmful to health is ultrasound. But the quality of such images is not sufficient for high-quality automated measurement of geometric parameters and diagnosis of deviations. The ultrasound image of the hip joint is evaluated by quantifying the exact values of the acetabular angle, the angle of inclination of the cartilaginous lip, and the location of the center of the femoral head. To get these geometric parameters, you need to have clear images of objects. And for the operation of automated computer measurement systems, it is necessary to use such methods of pre-digital image processing, which would give clear contours of objects. Known and available image processing algorithms, in particular contour selection, face problems in processing specific medical images. It is proposed to use the developed method of sharpening to further obtain high-quality contour lines of objects. A mathematical model of the method is presented, which is a formula for converting the intensity values of each pixel of a digital image. As a result of this method, the noise component of the image is reduced, and the intensity differences between the background and the objects are increased, and the width of these differences is one pixel. The algorithm of a sequence of processing of ultrasonic images and features of its application have resulted. The results of the developed set of methods are given. The paper presents the results of processing the real image of the hip joint, which visually confirms the quality of the selection of objects on view.